Directed Growth of Biomimetic Microcompartments. Issue 6 (6th February 2019) - Ivanov, Ivan; Lira, Rafael B.; Tang, T.‐Y. Dora; Franzmann, Titus; Klosin, Adam; da Silva, Lucas Caire; Hyman, Anthony; Landfester, Katharina; Lipowsky, Reinhard; Sundmacher, Kai; Dimova, Rumiana
Abstract: Contemporary biological cells are sophisticated and highly compartmentalized. Compartmentalization is an essential principle of prebiotic life as well as a key feature in bottom‐up synthetic biology research. In this review, the dynamic growth of compartments as an essential prerequisite for enabling self‐reproduction as a fundamental life process is discussed. The micrometer‐sized compartments are focused on due to their cellular dimensions. Two types of compartments are considered, membraneless droplets and membrane‐bound microcompartments. Growth mechanisms of aqueous droplets such as protein (condensates) or macromolecule‐rich droplets (aqueous two phase systems) and coacervates are discussed, for which growth occurs via Ostwald ripening or coalescence. For membrane‐bound compartments, vesicles are considered, which are composed of fatty acids, lipids, or polymers, where directed growth can occur via fusion or uptake of material from the surrounding. The development of novel approaches for growth of biomimetic microcompartments can eventually be utilized to construct new synthetic cells. Abstract : Growth of cell‐sized biomimetic microcompartments (droplets and vesicles) is essential for self‐reproduction, a key feature in bottom‐up synthetic biology. Droplets such as protein (condensates) or macromolecule‐rich droplets (aqueous two phase systems) and coacervates grow via Ostwald ripening or coalescence. Fatty acid, lipid, or polymer vesicles can grow via membrane fusion and/or uptake of material from the surrounding.